High intensity exercise training worsens alveolar destruction in pulmonary emphysema rats - Barnabé, Viviani; Lopes, Fernanda D. T.; M.Saraiva-Romanholo, Beatriz; Rosa, Clarice O.; Prado, Carla M.; Valenti, Vitor Engrácia [UNESP]; Martins, Milton de Arruda (GN1 Sistemas e Publicacoes, 2014)
OBJECTIVE: Investigation of standard intensities of physical exercise is important to better comprehend and develop rehabilitation programs for emphysema. We aimed to evaluate the effects of different intensities (moderate and high-intensity) of physical exercise on the development of a protease-induced (papain intratracheal instillation) emphysema in rats. METHODS: Male Wistar rats were randomly separated into ﬁve groups that received intratracheal instillation of papain solution or vehicle: (i) papain high intensity exercise, (ii) papain moderate exercise, (iii) saline high intensity exercise, (iv) saline sedentary and (v) papain sedentary. Forty days after intratracheal instillation, the exercise groups were submitted to an exercise-training protocol on a treadmill during 10 weeks, 5 days/week, at 0.9 km/h (Papain and saline high exercise), or at 0.6 km/h (papain moderate exercise).We measured respiratory system elastance and resistance, the collagen ﬁber lung parenchyma, and the pulmonary mean linear intercept. RESULTS: All animal groups that received papain instillation presented higher alveolar wall destruction compared to animals that received only saline solution. The papain high intensity exercise group presented higher values of mean linear intercept compared to emphysema groups that were trained at a moderate intensity or not submitted to exercise. CONCLUSION: High intensity exercise training worsened alveolar destruction in an experimental model of emphysema in rats when compared to moderate intensity exercise, or to no exercise.

OBJETIVO: A investigação de intensidades padrão de exercício físico é importante para melhor compreender e desenvolver programas de reabilitação para enﬁsema. Nosso objetivo foi avaliar os efeitos de diferentes intensidades (moderada e alta) de exercício físico sobre o desenvolvimento de enﬁsema induzido por protease (instilação endotraqueal de papaína) em ratos. MÉTODOS: Ratos Wistar machos foram divididos aleatoriamente em cinco grupos que receberam instilação intra-traqueal de solução de papaína ou veículo: (i) papaína, exercício de alta intensidade, (ii) papaína, exercício moderado, (iii) soro ﬁsiológico, exercício de alta intensidade, (iv) soro ﬁsiológico, sedentário e (v) papaína, sedentário. Quarenta dias após a instilação intra-traqueal os grupos de exercício foram submetidos a um protocolo de treinamento físico em esteira durante 10 semanas, 5 dias/ semana, a 0.9 km/h (papaína e solucão salina exercício de alta intensidade), ou em 0.6km/h (papaína exercício moderado). Medimos elastância do sistema respiratório e resistência, as ﬁbras de colágeno no parênquima pulmonar, e a intercepção linear média pulmonar. RESULTADOS: Todos os grupos de animais que receberam instilação de papaína apresentaram maior destruição da parede alveolar em comparação com animais que receberam apenas solução salina. O grupo papaína exercício de alta intensidade apresentou maiores valores de intercepto linear médio em comparação com grupos de enﬁsema que foram treinados em uma intensidade moderada ou não submetidos ao exercício. CONCLUSÃO: A alta intensidade de treinamento físico produziu mais destruição alveolar em um modelo experimental de enﬁsema em ratos quando comparada ao exercício de intensidade moderada, ou a nenhum exercício.